Prosthodontic Treatment Using Vital and Non Vital Submerged Roots-Two Case Reports - Shankar, Y. Ravi (JCDR Research and Publications (P) Limited, 2013)
Residual ridge resorption has been considered as an inevitable consequence after extraction of the teeth. There is a gradual loss of the alveolar bone due to the pattern of bone remodeling. In spite of the availability of newer treatment modalities like endodontic restoration and periodontic procedures for preservation of the remaining teeth they are not feasible for the patients in severe stages where restoration might not be possible. The only reliable method of preserving the remaining bone is by maintaining the functional health of the teeth. Over the years, many studies showed that roots which are fractured and left behind during extractions are retained into the alveolar bone with no evidence of pathosis. Over denture as a treatment option was developed in an effort to preserve the remaining alveolar bone by retaining the natural teeth or roots. In over denture treatment, the teeth selected as abutments are prone to caries and periodontal disease over a period of time, hence evolved the vital or non vital root submergence concept. After a thorough radiographic and clinical examination, few teeth without pathosis are retained that eventually are surgically submerged in the alveolar ridge. After healing, the over denture with reaining vital or non vital teeth preserve the integrity of the bone, making the treatment an effective and successfull preventive prosthodontic treatment.